FUNCTIONAL DEPENDENCE OF SETTLEMENTS AND ITS DEMOGRAPHIC COMPONENT IN THE TRANSITION PHASE OF THE DAILY URBAN SYSTEM - Filipović, Marko; Krunić, Nikola; Zhelenkova, Ekaterina (Journal of the Geographical Institute “Jovan Cvijić” SASA, 2022)
The transition period of post-socialist cities brought significant demographic and spatial changes within their daily urban systems (DUS). Functional transformations of the core, as well as functionally dependent settlements in the mentioned systems, had a significant impact on the daily mobility of the population. For the purposes of this paper, the example of Belgrade was taken as the core of the most significant DUS on the territory of Serbia, and beyond its borders. As a research time frame the focus is on the first intercensal period of the 21st century, taking into account social and economic changes in that period. The daily mobility of the labor force was used as a relevant indicator of the functional manifestation of the work center and the functional direction of the residential settlement. A model of the spatial manifestation of the workforce daily mobility was used as a basis for researching the structure, changes, and determining the boundaries of the territorial scope of the DUS. Based on the presented results, dynamic changes within the DUS of Belgrade were determined, which are manifested through an increase in its spatial and population coverage, as well as through the changes in the degree of functional dependence of the settlements that participate in it. Conclusions were drawn on the connection between the transformation of the DUS and its demographic component, as well as the factors that initiate the investigated changes.